The dermatological consequences of obesity. (21st July 2013) - Tobin, Anne‐Marie; Ahern, Tomas; Rogers, Sarah; Collins, Paul; O'Shea, Donal; Kirby, Brian
Abstract: Obesity is emerging as a global epidemic with at least 300 million people thought to be obese worldwide. This has implications for health professionals including dermatologists. Recent interest has focused on the role of obesity in psoriasis, but obesity is implicated in many dermatoses. Perhaps most worrying is emerging data which suggest that obesity may constitute a risk factor for the development of skin cancer. Its rising incidence ensures that obesity‐related skin disease will represent an increasing proportion of dermatologists' work load. In this article, we review dermatoses associated with obesity and review the epidemiology and treatment for obesity.